Optimizing Bamboo Utilization Through Hihid Product Design Innovation in Sukaluyu Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Sukaluyu Village in Tasikmalaya Regency benefits from abundant bamboo resources, a material traditionally used by the local community in their daily lives. However, the utilization of bamboo has remained largely conventional, hindering its market potential due to a lack of innovative design development. A key challenge is the limited variety in the design and form of bamboo handicrafts, particularly hihid (traditional hand fans), which possess considerable commercial promise. This community engagement initiative seeks to empower local residents by exploring novel, functional, and aesthetically pleasing forms of hihid suitable for everyday use and with wider market appeal. The methodology employed is Participatory Learning and Action (PLA), involving collaborative, practical training between the community members and the facilitator team. The results indicate that participants successfully learned the production techniques for both bamboo and plastic rattan hihid and were able to create diverse, functional, and visually attractive fan designs. This initiative has improved community skills and broadened local economic opportunities through innovative, bamboo-based craft products.